Pengaruh Kepuasan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada Kantor SAMSAT Lampung Tengah - Aropi Abdilah; Andiana Rosid; Nina Lelawati (Universitas Muhammadiyah Metro, 2024)
When the emotional state is pleasant or unpleasant where employees perceive their work tobe done and completed as well as possible, the workload and personal capacity of the workerare needed to complete the tasks assigned to him, so the aim of this research is to find outpartially or simultaneously about job satisfaction and workload on employee performance.This research design uses a quantitative approach, the sample used is 48 employees. Thesampling technique is census/saturation sampling and the data analysis technique usesvalidity, reliability, and decision making uses multiple regression tests with partial (t) andsimultaneous (f) test decisions. The research results prove that partially and simultaneouslythat job satisfaction and workload have a role in increasing employee performance at theCentral Lampung Samsat office